Infections with Bartonella spp. in free-ranging cervids and deer keds (Lipoptena cervi) in Norway. (June 2018) - Razanske, Irma; Rosef, Olav; Radzijevskaja, Jana; Klepeckiene, Kamile; Lipatova, Indre; Paulauskas, Algimantas
Highlights: Bartonella DNA was detected in 10.5%–35.9% cervids and 85% deer keds. Two Bartonella lineages in Norwegian cervids and deer keds were detected. One lineage of Bartonella sp. is transmitted by L. cervi. For other lineage the possible vectors still remain unknown. Abstract: Bartonella bacteria are arthropod-borne and can cause long-term bacteremia in humans and animals. The predominant arthropod vectors and the mode of transmission for many novel Bartonella species remain elusive or essentially unstudied. The aim of this study was to investigate the prevalence of Bartonella spp. in Norwegian cervids and deer keds ( Lipoptena cervi ) and to characterise the bacteria by sequencing of the partial gltA gene and 16 S–23 S rRNA intergenic spacer region (ITS) in order to evaluate a possible transmission route. A total of 260 spleen samples and 118 deer keds were collected from cervids by hunters in the Southern part of Norway. Bartonella DNA was detected in 10.5% of spleen samples of roe deer (n = 67), in 35.1% red deer (n = 37), in 35.9% moose (n = 156), and in 85% pools of adult wingless deer ked (n = 59). Two Bartonella lineages were identified based on phylogenetic analysis of the gltA gene and ITS region sequences.